Investigating the Network Characteristics of Two Popular Web-Based Video Streaming Sites - Almatarneh, Feras Mohammed (European Scientific Journal, ESJ, 2017)
The determinants of the strategies to be employed by video streaming sites are application (mobile devices or web browsers) and container of the video application. They affect video streaming network characteristics, which is often the traffic flow, and its quality. It is against this background that studies on streaming strategies suggested the need to investigate and identify the relationship between buffer time, video stream protocol, packet speed and size, upload time, and waiting period, specifically to aid network administrative support in case of network traffic bottlenecks. In view of this, this study investigates the network characteristics of YouTube and Vimeo, using experimental methodology, and involving WireShark as network analyzer. Google Chrome and Firefox are the web browsers employed, while packet size, protocols, packet interval, TCP window size and accumulation ratio are the metrics. Short ON-OFF, Long ON-OFF, and No ON-OFF cycles are the three streaming strategies identified. It is further shown that both Vimeo and YouTube employ these strategies but the choice depends on the container of the video streamed.